The Influence of Motivation, Competence and Employee Performance on Job Satisfaction of Sarana Jaya Building Store Employees, Probolinggo Regency - Tyas, Yayuk (Central Research Institute for Agriculture (CeRIA), 2024)
This research was conducted with the aim of determining the variables of motivation, compensation, and employee performance that influence employee job satisfaction at Sarana Jaya Building Store in Probolinggo Regency. In this study, the type of research used was Quantitative Descriptive. The variables used include independent (explanatory) and dependent (response) variables. The independent variables include: (1) motivation, (2) compensation, (3) employee performance. While the dependent variable is job satisfaction. The population in this study is all branch employees of UD. Citra Indah in Probolinggo City, namely TB. Sarana Jaya in Probolinggo Regency, totaling 40 employees. The sample taken consisted of 40 employees as respondents using saturated sampling. The data sources used include (1) primary data (2) secondary data. The analysis methods used include: descriptive statistics, validity and reliability tests, classical assumption tests, multiple regression analysis, and partial tests (t-test). The results of this study indicate that (1) the motivation variable has a significant effect on job satisfaction. (2) the compensation variable has a significant effect on job satisfaction. (3) the performance variable has a significant effect on job satisfaction